Patient Outcome Study of Concurrent Chemoradiation, External Beam Radiotherapy, and High-Dose Rate Brachytherapy in Locally Advanced Carcinoma of the Cervix. Issue 6 (1st July 2010) - Forrest, Jennifer Louise; Ackerman, Ida; Barbera, Lisa; Barnes, Elizabeth A.; Davidson, Melanie; Kiss, Alex; Thomas, Gillian
Abstract : Introduction: A regimen of concurrent chemoradiation for definitive treatment of cervical cancer is widely used. This retrospective review has been conducted to determine the outcomes and late toxic effect associated with the specific regimen of whole-pelvic external beam radiotherapy of 45 Gy in 25 fractions with parametrial boosts of 5.4 or 9 Gy and HDR brachytherapy (BT) of 30 Gy in 5 fractions to point A delivered by tandem and ring. This protocol is accepted by the Gynecological Oncology Group and endorsed by the American Brachytherapy Society, but no late toxic effect data have been reported. Materials and Methods: The electronic records of sequential patients treated definitively at the Sunnybrook Odette Cancer Centre between January 2006 and December 2008 were reviewed. Patient-, tumor-, and treatment-related details (including external beam radiotherapy, BT, and chemotherapy) were obtained. Outcome measures included disease-free status, dates and sites of first recurrence, survival, and grade 3/4 late toxic effect results (Common Terminology Criteria Adverse Events 3.0 criteria). Exclusion criteria were no follow-up or a planned alternative regimen. Results: One hundred twenty-two patients (+11 excluded) were treated with a median follow-up of 18 months from diagnosis. The actuarial 2-year disease-free survival rate was 70%. The median time to recurrence was 8 months (range, 2-22 months). The median time to toxic effect was 10 months (range 4-27 months). Grade 3/4 toxic effect was observed in 13 patients (11%). The actuarial grade 3/4 toxic effect rate at 2 years was 14%. Conclusions: Despite a relatively short follow-up, the toxicity of this regimen seems high compared with other retrospective series, although pelvic control is good. Consideration should be given to a reduction in BT dose alternatively when feasible image-guided BT may allow maintenance of tumor dose with reduced dose to organs at risk.